Analisis Kesalahan Numerasi Peserta Didik dalam Menyelesaikan Soal Assesmen Kompetensi Minimum - Yusuf, Rizky Mauldan Muhammad; Ratnaningsih, Nani (Jurnal Paedagogy, 2022)
This study aims to analyze student errors in solving Minimum Competency Assessment (AKM) questions. This research was carried out in class XI MIPA 1 SMA Islam Cipasung with the instrument that had been prepared, namely the numeracy ability test sheet. This study uses a descriptive method with a qualitative approach. By means of purposive sampling, the determination of the subject was based on the test results of the students who answered all the numeracy indicators, so that 3 subjects were taken. The research instrument includes test sheets, and unstructured interviews and the data analysis technique used is qualitative descriptive analysis. The results showed that S - 8 made mistakes in analyzing the information in the question, S - 33 made mistakes in analyzing the information obtained and made mistakes in making decisions from the conclusions obtained.